Inversion and allozyme polymorphism show contrasting patterns of microgeographical population structure in a natural population of Drosophila buzzatii from Argentina - Fernández Iriarte, P.J. (2002)
Second chromosome inversions and genotypic frequencies at seven allozyme loci were determined in a natural population of the cactophilic species Drosophila buzzatii that uses as breeding sites the necrotic cladodes of the prickly pear Opuntia quimilo and the rotting stems of cardón, Trichocereus terschekii. Different processes govern the evolutionary fate of inversion and allozyme polymorphisms. A pattern of heterotic balance for inversions seems to be acting uniformly in each breeding site and could depend on different regimes of density-dependent selection within cactus hosts. Patterns of variation of allozymes revealed significant heterogeneity in allele frequencies for Esterase-1 (Est-1) among O. quimilo rots and Aldehyde oxidase (Aldox) and Xanthine dehydrogenase (Xdh) among T. terschekii substrates and showed gene-cactus effects only for Esterase-2 (Est-2). Consistent and significant excesses of homozygotes were detected at both the within-rot and in the total population levels that could be accounted for by diversifying selection among individual breeding sites.